1976
DOI: 10.1002/ijc.2910170305
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rates of specific histological types of lung cancer in Singapore Chinese dialect groups, and their aetiological significance

Abstract: Significant differences in the incidence levels of lung cancer have been observed among major Chinese dialect groups or communities (Kokkien, Teochew and Cantonese) in Singapore. Among males, the incidence rate is highest in the Hokkiens (age-standardized incidence rate per 100,000 persons per year in Hokkien 67.8, Teochew 55.3, Cantonese 54.0) and among females, it is highest in the Cantonese (Hokkien 12.4, Teochew 12.8, Cantonese 27.2). The present investigation was undertaken to determine the incidence rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
1

Year Published

1977
1977
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 8 publications
1
19
1
Order By: Relevance
“…In comparison to European series the proportion of adenocarcinoma has been high in Hong Kong (Chan & MacLennan, 1977) and also in Singapore (Law et al, 1976). In our series it amounted to 26% in men and 490 in women.…”
Section: Histological Typecontrasting
confidence: 57%
See 1 more Smart Citation
“…In comparison to European series the proportion of adenocarcinoma has been high in Hong Kong (Chan & MacLennan, 1977) and also in Singapore (Law et al, 1976). In our series it amounted to 26% in men and 490 in women.…”
Section: Histological Typecontrasting
confidence: 57%
“…In Singapore bronchial cancer, especially adenocarcinoma, occurs most frequently among Cantonese females (Law et al, 1976) and a case-control study showed that 18/39 Cantonese female victims were nonsmokers (MacLennan et al, 1977). Seventysix per cent of the Hong Kong population were classified Cantonese in the 1971 census (Hong Kong, 1972).…”
mentioning
confidence: 99%
“…Lung cancer rates are high among non-smoking women in certain areas of China due to indoor cooking with poorly vented coal-fueled stoves (Fraumeni and Mason, 1974;Law et al, 1976). However, the relative risk for lung cancer associated with cigarette smoking is lower among women in Japan (Stellman et al, 2001) and China (Liu et al, 1998;Niu et al, 1998;Yuan et al, 1996) than in the West.…”
Section: Lung Cancer Risk In Asians Versus Caucasiansmentioning
confidence: 99%
“…Lung cancer in Hong Kong Chinese is peculiar in that there is a high incidence in females, a fact shared by Chinese populations in other parts of the world, including China, Singapore, California and Hawaii (China, 1979;Law et al, 1976;Waterhouse et al, 1976). This results in a very low male:female ratio of about 2:1.…”
mentioning
confidence: 99%